2022
DOI: 10.1016/j.str.2021.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Small, but powerful and attractive: 19F in biomolecular NMR

Abstract: Nuclear magnetic resonance (NMR) spectroscopy is a versatile tool for probing structure, dynamics, folding, and interactions at atomic resolution. While naturally occurring magnetically active isotopes, such as 1 H, 13 C, or 15 N, are most commonly used in biomolecular NMR, with 15 N and 13 C isotopic labeling routinely employed at the present time, 19 F is a very attractive and sensitive alternative nucleus, which offers rich information on biomolecules in solution and in the solid state. This perspective sum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 101 publications
0
42
0
Order By: Relevance
“…Of particular importance, the differences in the biomechanical properties of the IVD are likely to result predominantly from the IVD structural organization rather than compositional variation [ 106 ]. Structural and biomechanical studies have shown that elastic fibers contribute significantly to the structure and function of IVDs; however, more studies using advanced technologies are required to fully characterize their mechanical properties, including in health and disease conditions [ 107 , 108 , 109 , 110 ]. While recent studies have identified that elastic fiber breakdown products, such as elastokines, play a role in the development of a variety of diseases, i.e., supravalvular aortic stenosis and the Williams-Beuren syndrome, the impact of the process on IVD pathologies is yet unclear [ 111 , 112 ].…”
Section: Future Outlookmentioning
confidence: 99%
“…Of particular importance, the differences in the biomechanical properties of the IVD are likely to result predominantly from the IVD structural organization rather than compositional variation [ 106 ]. Structural and biomechanical studies have shown that elastic fibers contribute significantly to the structure and function of IVDs; however, more studies using advanced technologies are required to fully characterize their mechanical properties, including in health and disease conditions [ 107 , 108 , 109 , 110 ]. While recent studies have identified that elastic fiber breakdown products, such as elastokines, play a role in the development of a variety of diseases, i.e., supravalvular aortic stenosis and the Williams-Beuren syndrome, the impact of the process on IVD pathologies is yet unclear [ 111 , 112 ].…”
Section: Future Outlookmentioning
confidence: 99%
“…Towards understanding the rate of unmasking inside the live cells, we developed an in-cell time-resolved 19 F-NMR to monitor the rate of POM group unmasking (Figure 6). 19 F-NMR is uniquely suited for this task due to the high receptivity of 19 F, low background in biological samples and remarkable sensitivity of 19 F chemical shifts to their chemical environment [53][54] . The latter means that even the distant fluorine of MN551 could act as a reporter for the presence of the masking group on the phosphotyrosine moiety.…”
Section: Scheme 5 Synthesis Of Mn551 Prodrugsmentioning
confidence: 99%
“…19 F NMR screening, one of the available biophysical tools, [1–3] is a highly effective and well‐established hit‐finding approach [4–10] . The ligand‐observed 19 F NMR screening method known as FAXS (Fluorine chemical shift Anisotropy and eXchange for Screening) can be performed in a direct or competition mode and allows the measurement of the binding affinity of the identified hits [4] .…”
Section: Introductionmentioning
confidence: 99%